P150 Impact of radon SPA on pain and the immune system of patients with musculoskeletal disorders. (March 2019) - Becker, I; Donaubauer, A-J; Klein, G; Fournier, C; Fietkau, R; Frey, B; Gaipl, US
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: The pain reducing effects of certain natural springs containing the radioactive noble gas radon have been described for centuries. Today, one expects that small cumulative dose of radiation of about 0.3 mSv originating from radon progeny impacts on the immune system and bone metabolism of patients suffering from chronic painful degenerative and/or inflammatory diseases. However, osteoimmunological analyses of patients during radon spa were lacking. Objectives: We initiated the observational and explorative RAD-ON01 study to analyse for the first time the impact of radon spa on the immune status in the whole blood of 100 patients. Methods: Whole blood of the patients was drawn before and at weeks 6, 12 and 30 after therapy. Deep immunophenotyping was performed by multicolour flow cytometry and cytokine analyses by ELISA. Results: The RAD-ON01 study confirmed a long-lasting pain reduction. While the major immune cells were only marginally affected, in particular regulatory T cells and dendritic cells were temporarily increased and activation markers on immune cells were decreased. Further, a decrease of serum markers related to bone erosion was observed. The cytokine analyses showed that temporarily increased TGFβ following radon spa correlates with reduced pain perception of the patients. To exclude placebo effects, in November 2018 the RAD-ON02 study (EUDRACT: 2016-002085-31) started. With this prospective, temporarily placebo-controlled and double- blinded trial the evidence level of radon spa application and knowledge on osteoimmunological modes of action of radon should be improved. Conclusions: We conclude that patients with musculoskeletal disorders do benefit from radon spa and that osteoimmunological mechanisms are modulated by exposure of the patients to very low doses of radiation. Future randomized studies should improve the evidence level for radon as therapeutic option for chronic painful degenerative and/or inflammatory diseases. Acknowledgements: This work was supported by the German Federal Ministry of Education and Research (GREWIS, 02NUK017G and GREWIS-alpha, 02NUK050E), the Bayerisches Staatsbad Bad Steben GmbH, the Landesamt für Gesundheit und Lebensmittelsicherheit Bayern, and the EU (FP7 Nuclear Fission, Safety and Radiation Protection; FP7–249689). Disclosure of Interest: None declared.